Religion, Education, and Maintaining Ethno-religious Harmony in Sanggau, West Kalimantan - Ruslan, Ismail; Amri, Faizal; Yusriadi, Yusriadi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to explore the role of religion and education in maintaining inter-ethnic harmony in Sanggau, West Kalimantan, Indonesia. Sanggau, with its ethnic diversity including Malays, Dayaks, Chinese and others, provides a rich context for understanding how inter-group harmony can be maintained through religious and educational interventions. This study uses qualitative methods, including in-depth interviews with religious leaders, community leaders and teacher, as well as observation and documentation of religious, educational and social activities in Sanggau. The data is then recorded and assigned a code. It is subsequently grouped according to broader categories, with reference to the purpose of the research. The relationship between the themes within the data is then narrated in order to facilitate the construction of research conclusions. These conclusions are then associated with the results of previous studies and relevant theories. The findings of this study indicate that small-scale conflicts over religious issues are common in the Sanggau. The conflict arose because of the multi-religious and multi-ethnic situation. Conflicts arose over the construction of places of worship, religious changes and interfaith marriages. However, these conflicts have been resolved through ethno-religious and educational approaches. Group identity is used to strengthen the bonds of fraternity, as expressed in the phrase